Analysis of the causes of unsatisfactory cooling of return network water in heating substations - Razumkova , Katsiaryna; Laskowski , Rafał; Smyk , Adam (Instal, 2019)
The article presents the reasons for unsatisfactory cooling of network water in some heating substations. The analysis was based on measurement data currently being carried out at the heating substations. Additional parameters have been indicated, the measurement of which would enable full diagnostics of the reasons for the temperature increase in DH network return water.
Keywords: district heating system; heating substation; DH network water parameters